PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 003 SUNGAI GUNTUNG KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Munaria, Munaria; Alim, Jesi Alexander; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac : this research was purpose to improve learning result IPA Class IV SD Negeri 003 Sungai Guntung with the application learning model of Problem Based Instruction (PBI) to improve learning result IPA fourth grade students of SD Negeri 003 Sungai GuntungKecamatanRengatKabupaten Indragiri Hulu 2014/2015 school year was 22 people consist of 12 men and 10 women. This research forms of classroom action research collaborative with two cycles. The research data shows that student learning result obtained that fact the increase in the average of student learning before action is 56, 14 and increased in the first cyclus become 72,72 the differences increase from the previous test scores of 16,22% in cyclus II the average students learning result increased to 61,50 there was increase from cyclus I to the cyclus II of 22,72. Improving student learning result as a whole by 35,79 %. Improving students learning result support by : (a). The percentage of teachers in cyclus I of activity by 85,71% with enough categories, increased in cyclus II become 92,85% with good categories. (b). The percentage of student in cyclus I of activity by 83,65% with good categories, increased in cyclus II. The cyclus II student activity is 90,38% with very good categories, increased in cyclus II. The cyclus II student activity is 90,38% with very good categories, there was increase student activity from the previous with differences 6,73%. It can be concluded that the hypothesis in the this study is “if the applied learning model of Problem Based Instruction (PBI) to improve learning result IPA Class IV SD Negeri 003 Sungai GuntungKecamatanRengatKabupaten Indragiri Hulu” to acceptable.Keywords :Leraning Model Problem Based Instruction (PBI) learning result of IPA